Histological effects of zinc-supplemented diet in selected organs of male Sprague Dawley rats - Hamzah, Hazilawati (2015)
Zinc is the second most essential trace element needed for bodily functions, after iron. The diverse functions of zinc lead to zinc tablets being the most readily available supplements worldwide for both human and animal nutrition. This study aims to investigate the histological effects of zinc supplemented diet in selected organs of rats. Fourteen male Sprague Dawley were divided into two groups, either the control group (n=6) or with 12 mg/kg zinc oxide supplementation in their drinking water (n=8). Monitoring of the body weight, feed and water intake were done weekly, and blood collection for complete blood count and plasma biochemistry was done monthly. At the end of the experimentation period, the rats were humanely sacrificed and post-mortem was conducted. Histology was done in a routine manner. Results showed increased plasma amylase level in zinc supplemented rats, during week 8 and week 12 of experimentation. Histology revealed no cellular changes in the liver, and increased spermatogenesis in the testes. However, in the pancreas, the zinc supplemented group showed changes in both the acini and the islet of Langerhans, namely vacoulation and coagulation of the acinar cells, as well as hypercellularity and fatty necrosis of the islet of Langerhans. Zinc supplementation may have led to elevated pancreatic zinc concentration, which leads to hyperamylasemia. The cellular damage caused by imbalance of zinc homeostasis due to zinc supplementation causes physiological compensatory mechanism to produce more amylase in other structures to compensate less production of amylase in the exocrine pancreas.